Transform-based coding method for remote sensing hyperspectral data compression - Yuzkiv, Ruslan; Sergeev, Vladislav (Procedia engineering, 2017)
A version of the transform-based coding compression method for remote sensing hyperspectral data is proposed. New version is based on the calculation of a separate quantization matrix for each image and the preliminary removal of low-frequency components in the input data. Larger compression ratios are shown in comparison with the layered JPEG algorithm with the same mean square recovery error.